2018
DOI: 10.1111/ases.12450
|View full text |Cite
|
Sign up to set email alerts
|

Video‐assisted thoracoscopic surgery can help enable the complete resection of a mediastinal tumor caused by immunoglobulin G4‐related disease and avoid the need for postoperative medication: A case report

Abstract: Immunoglobulin (Ig) G4-related disease has various clinical signs and symptoms, and steroidal therapy with corticosteroids has been found to be effective for treatment. Few cases of IgG4-related disease associated with paravertebral tumor have been reported, and there have been no reports on complete resection of such a tumor. Here, we report a case of IgG4-related disease associated with a paravertebral tumor that was successfully resected without the need for postoperative medication. An 84-year-old woman wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…IgG4-RD cases with single-organ involvement, such as the present case, are rare, with only one case of IgG4-RD occurring in the mediastinum previously reported [2]. Tissue sampling is necessary to diagnose IgG4-RD, and thus, a surgical biopsy was inevitable in this case.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…IgG4-RD cases with single-organ involvement, such as the present case, are rare, with only one case of IgG4-RD occurring in the mediastinum previously reported [2]. Tissue sampling is necessary to diagnose IgG4-RD, and thus, a surgical biopsy was inevitable in this case.…”
Section: Discussionmentioning
confidence: 72%
“…Immunoglobulin G4-related disease (IgG4-RD), a systemic autoimmune disease, is characterized by enlarged, massive, and thickened lesions in various body organs, laboratory ndings of high serum IgG4 concentrations, marked lymphocytic and IgG4-positive plasma in ltration, and brosis of the tissues [1]. It affects nearly every organ, and its clinical course varies, depending on the involved organ; however, few reports exist on its occurrence in the mediastinum [2]. In rare cases, when the mediastinum is involved, the diagnosis is di cult.…”
Section: Introductionmentioning
confidence: 99%
“…Four cases of IgG4-RD occurring exclusively in the posterior mediastinum have been reported in previous literature (Table 1 ). In all cases, percutaneous biopsy was difficult, and in two cases, resection was performed as the intraoperative rapid pathological examination did not rule out malignancy [ 3 , 4 ]. Likewise, in two cases, biopsy was performed only for diagnostic purposes [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gopalsamy et al (11) reported that the inhibition of IL-1β and IL-6 expression effectively inhibits the pain stress response. In the study of different operation methods for mediastinal tumor resection, Uchida et al (23) and Kamata et al (24) found that VATS is the first choice for tumor resection. In the present study, a judgement of pain stress indicators was added in the confirmation of results, which enhanced the real-time control of operation.…”
Section: Discussionmentioning
confidence: 99%